2018
DOI: 10.1002/elsc.201700153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of copper on expression of methane monooxygenases, trichloroethylene degradation, and community structure in methanotrophic consortia

Abstract: Copper plays a key role in regulating the expression of enzymes that promote biodegradation of contaminants in methanotrophic consortia (MC). Here, we utilized MC isolated from landfill cover to investigate cometabolic degradation of trichloroethylene (TCE) at nine different copper (Cu2+) concentrations. The results demonstrated that an increase in Cu2+ concentration from 0 to 15 μM altered the specific first‐order rate constant k1,TCE, the expression levels of methane monooxygenase (pmoA and mmoX) genes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
(86 reference statements)
1
4
0
Order By: Relevance
“…Previous research has reported a correlation between methane oxidation rates in Ob3b and increasing concentrations of Cu in the growth medium as well as the expression of MMOs [34][35][36][37]. Similarly, this study observed an enhancement in the methane and oxygen utilization rates for each concentration of Cu used to grow the M. trichosporium OB3b, as depicted in Figure 1b and c, respectively.…”
Section: Effects Of Cu On Growth and Methane Utilizationsupporting
confidence: 81%
See 2 more Smart Citations
“…Previous research has reported a correlation between methane oxidation rates in Ob3b and increasing concentrations of Cu in the growth medium as well as the expression of MMOs [34][35][36][37]. Similarly, this study observed an enhancement in the methane and oxygen utilization rates for each concentration of Cu used to grow the M. trichosporium OB3b, as depicted in Figure 1b and c, respectively.…”
Section: Effects Of Cu On Growth and Methane Utilizationsupporting
confidence: 81%
“…These results suggest that an increase in the rate of methane uptake is directly proportional to the increased growth rates and Cu concentration in the culture medium. As such, published reports have suggested that methane uptake rates may continue to increase until the Cu concentration reaches to a toxic concentration (>4.2 mM) for most well-studied methanotrophs [12,35,38].…”
Section: Effects Of Cu On Growth and Methane Utilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterotrophic richness has been shown to enhance methane oxidation activity by MOB (Ho et al, 2014), as accompanying organisms can either remove inhibiting substances (e.g., methanol) or provide stimulating factors (e.g., essential nutrients such as cobalamin; Stock et al, 2013;Iguchi et al, 2015;Veraart et al, 2018;Singh et al, 2019). On the other hand, MOB also select for certain heterotrophs by providing organic metabolites (e.g., acetate) or by removing toxic compounds (e.g., formaldehyde; Morris et al, 2013;van der Ha et al, 2013;Oshkin et al, 2015;Gilman et al, 2017;Xing et al, 2018). Indeed, MOB play an integral role in transferring methane-derived carbon and other metabolites to the microbial pool and higher trophic levels of the food web (Jones and Grey, 2011;Sanseverino et al, 2012;Agasild et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although variations in temperature resulting from seasonal fluctuations may be quite limited and the bottom water temperature is usually stable (2-7 • C) for deep marine environments, it may be influenced by ocean currents [26]. The temperature sensitivity of methanotrophs is susceptible to other environmental factors, such as water content and sediment characteristics [27][28][29], and thus, the response of aerobic methane oxidation patterns to temperature in terrestrial ecosystems such as rice fields, forests, or permafrost soils may be quite different from that in marine environments [30,31]. Currently, exact knowledge regarding temperature controls on marine aerobic methane oxidation is still missing.…”
Section: Introductionmentioning
confidence: 99%